Transforming Education with ChatGPT: Advancing Personalized Learning, Accessibility, and Ethical AI Integration - Asy'ari, Muhammad; Sharov, Sergii (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
The integration of artificial intelligence (AI) in education, exemplified by tools like ChatGPT, represents a transformative shift in teaching and learning methodologies. This study explores ChatGPT’s role in advancing personalized learning, empowering educators, and enhancing accessibility within educational ecosystems. Using a systematic literature review supported by bibliometric analysis, the paper identifies key trends and insights into AI-driven educational technologies. Findings demonstrate ChatGPT's capacity to personalize instruction by generating adaptive content, delivering real-time feedback, and facilitating curriculum development. It also alleviates educators' workloads through automated grading, lesson planning, and administrative support. However, challenges such as ethical concerns regarding data privacy, inherent AI biases, and potential over-reliance on automation hinder its widespread adoption. The study emphasizes the necessity of ethical guidelines, transparency, and balanced AI integration to mitigate these risks. In conclusion, ChatGPT holds substantial potential for improving educational outcomes by fostering inclusive, adaptive, and efficient learning environments. Future efforts should focus on refining AI technologies to reduce biases, uphold data privacy, and equip educators with the skills needed to effectively integrate AI into pedagogical practices. Responsible and ethical implementation will be key to unlocking ChatGPT's full potential in education.